Empowering Of Local Communities Through English Training For Digital Marketing And E-Commerce - Imran, Fathurrahman; Syahrir, Syahrir; Supriadin, Supriadin (Abdi Masyarakat, 2025)
Empowering MSMEs in Karang Bongkot Village through training in business English, digital marketing, and e-commerce aims to increase production capacity, digital marketing capabilities, and international business communication. This program responds to the challenges of low technology adoption and limited English language skills for national and international market penetration. The training is conducted using a blended learning method and supported by production technology innovations. Results show an increase in production capacity of up to 250 units per month, 100% adoption of Facebook and Instagram by participants, increased sales, and strengthened product branding. The main challenges are mastering English and advanced digital marketing, which require ongoing guidance. This program serves as the foundation for SME transformation toward broader and more competitive markets.